Is Preoperative Urine Human Chorionic Gonadotropin (hCG) Testing Necessary for Pediatric Patients Before Oral and Maxillofacial Surgery Procedures With Sedation? - Flanagan, Sarah G.; Green, Mark A. (Journal of oral and maxillofacial surgery, 2023)
Human chorionic gonadotropin (hCG) testing is performed prior to surgical procedures to ensure patient and fetal safety. The purpose of this study was to evaluate the utility of routine pregnancy testing prior to elective outpatient oral and maxillofacial surgery procedures being performed with intravenous sedation (IVS). A retrospective cohort study was implemented assessing hCG testing in postmenarche females who underwent elective outpatient oral surgery procedures scheduled with IVS at a tertiary care institution. Medical records were used to identify eligible subjects aged 12 to 45 years. The primary predictor variable was age, and the primary outcome variable was urine hCG test result. Age was divided into groups to reflect early adolescence (12 to 14 years), mid-adolescence (15 to 17 years), late adolescence/early adulthood (18 to 24 years) and adulthood (25+ years). Secondary outcome variables included inability to void for hCG testing, change in anesthetic, case cancellation or rescheduling and were measured over a 2 year period. Descriptive statistics were performed. Relative risk (RR) and Cochran-Armitage test for trend were calculated to determine the statistical significance of age on inability to void. The sample consisted of 5,006 females, with a median age (IQR, range) of 18.0 (3.6, 12.0 to 43.6) years. There was one positive urine hCG result providing a preoperative pregnancy rate of 0.02%. Fourteen of 1,195 subjects (1.2%) over a 2 year period were unable to provide a urine hCG sample. There was a statistically significant trend in inability to void as age groups got older (P = .001). Patients aged 12 to 17 years had an increased risk of being unable to void compared to patients 18 years and older (RR: 14.30, 95% CI: 1.88 to 108.99, P = .01). The total cost of testing over the 11 year observation period was $9,019.59. The risk of surgical cancellations and delayed care due to patients' inability to void preoperatively plus a lack of any positive preoperative urine hCG findings in patients under 18 years of age in this study, call into question the necessity of routine preoperative hCG screening in pediatric patients presenting for IVS for elective outpatient oral and maxillofacial procedures.